2021
DOI: 10.21037/atm-21-3272
|View full text |Cite
|
Sign up to set email alerts
|

Soluble LRIG2 is a potential biomarker for type 2 diabetes mellitus

Abstract: Background: Early diagnosis and treatment of type 2 diabetes can delay the onset of microvascular and macrovascular complications. Therefore, the identification of a novel biomarker for diagnosing diabetes is necessary. In the present study, the role of serum soluble leucine-rich repeats and immunoglobulin like domains 2 (sLRIG2) was investigated as a diagnostic biomarker of type 2 diabetes.Methods: A total of 240 subjects with newly diagnosed type 2 diabetes (n=80), prediabetes (n=80), or normal glucose toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…In our study, we found that there was proportionate increase in NLR with increase in 24 hours urine albumin excretion. Similar to our finding, Kahraman et al [30] found a linear relationship between NLR and 24 hours urine albumin excretion. In our study, there was a linear positive correlation between serum creatinine and NLR.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, we found that there was proportionate increase in NLR with increase in 24 hours urine albumin excretion. Similar to our finding, Kahraman et al [30] found a linear relationship between NLR and 24 hours urine albumin excretion. In our study, there was a linear positive correlation between serum creatinine and NLR.…”
Section: Resultssupporting
confidence: 93%
“…Kahraman et al . [ 30 ] reported that there was a significant positive correlation between NLR and serum creatinine in their study. In the present study, patients with low eGFR had high NLR levels.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“… 21 Full length LRIG2 is a plasma membrane protein but a soluble cleaved form has also been described. 38 LRIG2 enhances tumor growth in diverse tissues, including brain and skin, a property conferred in part by modulating growth factor signaling. 22 , 39 , 40 Mouse studies have also implicated LRIG2 in axon guidance during central nervous system development and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous Lrig2 or Hpse2 mutant mice both have abnormally patterned bladder nerves (Roberts et al, 2019). Full length LRIG2 is a plasma membrane protein but a soluble cleaved form has also been described (Kim et al, 2021). LRIG2 enhances tumour growth in diverse tissues, including brain and skin, a property conferred in part by modulating growth factor signaling (Rondahl et al, 2013;Dong et al, 2020;Hoesl et al, 2019).…”
Section: Insights Into Lrig2 Associated Human Bladder Diseasementioning
confidence: 99%